2019
DOI: 10.1016/j.buildenv.2018.10.045
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of formaldehyde concentration in residences and the development of a model for the prediction of its emission rates

Abstract:  CO2 concentration was used as the tracer gas to calculate the indoor ventilation airflow rate;  Monte-Carlo simulations were conducted for sensitivity analysis;  A time-averaged effective emission rate predicts the formaldehyde emission rate in residences;  Occupant activity was taken into account to calculate the emissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…An additional problem in quantifying whole-house emission rates of formaldehyde is that some studies account for its apparent indoor loss rate while others do not. Formaldehyde indoor loss is a very poorly understood physicochemical process, but the limited observational evidence suggests that the first order loss coefficient for formaldehyde is in a range from 0.15 to 0.88 h –1 , similar to the ACH values measured in homes. Often, this loss is ignored when applying a steady-state mass balance model to derive emission rates from measured indoor concentrations, ,, resulting in significant underestimation of formaldehyde whole-house emission rates . Ignoring this loss causes potential obfuscation of how formaldehyde emission rates vary with the ACH.…”
Section: Introductionmentioning
confidence: 99%
“…An additional problem in quantifying whole-house emission rates of formaldehyde is that some studies account for its apparent indoor loss rate while others do not. Formaldehyde indoor loss is a very poorly understood physicochemical process, but the limited observational evidence suggests that the first order loss coefficient for formaldehyde is in a range from 0.15 to 0.88 h –1 , similar to the ACH values measured in homes. Often, this loss is ignored when applying a steady-state mass balance model to derive emission rates from measured indoor concentrations, ,, resulting in significant underestimation of formaldehyde whole-house emission rates . Ignoring this loss causes potential obfuscation of how formaldehyde emission rates vary with the ACH.…”
Section: Introductionmentioning
confidence: 99%
“…In the underground platform of subway station, the concentrations of TVOCs or PM10, PM2.5 were higher than the regulated standards stipulated by Taiwan′s Environmental Protection Administration [16]. Analysis found that indoor formaldehyde concentration of 30.12μg/m 3 was slightly higher than that of outdoor 27.80μg/m 3 [17], and the concentration of formaldehyde in indoor were 0.21mg/m 3 , 0.11mg/m 3 , 0.04mg/m 3 after 3 months, 6 months, 12 months of decoration [18] which decreased with the passage of time [19,20].…”
Section: Introductionmentioning
confidence: 88%
“…The Treaty on the Functioning of the European Union and Directive 2010/75/EU of the European Parliament and of the Council of 24 November 2010 on industrial emissions (regarding integrated pollution prevention and control), in particular, Article 13 (5) on Best Available Techniques (BAT), constitutes the reference for setting permit conditions for installations referred to in Chapter II of Directive 2010/75/EU [8]. Many studies have been done on formaldehyde emissions from different processes [9][10][11].The competent authorities of an EU Member State should set emission limit values to ensure that, under normal operating conditions, emissions do not exceed the emission levels associated with the best available techniques as specified in BAT; the levels for total volatile organic carbon (TVOC) and formaldehyde (FA) are given in [12] and are for TVOC < 5-30 mg/m 3 and for formaldehyde 2-5 mg/m 3 .…”
Section: Eu Directives On Industrial Emissionsmentioning
confidence: 99%